2018
DOI: 10.1523/jneurosci.0074-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Myelination of Parvalbumin Interneurons Mediated by Axonal Morphological Plasticity

Abstract: Axonal myelination of neocortical pyramidal neurons is modulated dynamically by neuronal activity. Recent studies have shown that a substantial proportion of neocortical myelin content is contributed by fast-spiking, parvalbumin (PV)-positive interneurons. However, it remains unknown whether the myelination of PV interneurons is also modulated by intrinsic activity. Here, we used cell-type-specific Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) in adult mice to activate a sparse populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 21 publications
6
94
0
Order By: Relevance
“…However, myelin is also present within the cortical grey matter, where it is heterogeneous and patchy along projection neurons 10,11 . Moreover, a large fraction of the parvalbumin-positive interneuron axons are myelinated 1214 , even though their typical short distance to their target cells has been estimated to cause insignificant conduction delay times 13 . Oligodendrocyte lineage cells can myelinate axons in an activity dependent manner and influence their conduction velocity properties 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…However, myelin is also present within the cortical grey matter, where it is heterogeneous and patchy along projection neurons 10,11 . Moreover, a large fraction of the parvalbumin-positive interneuron axons are myelinated 1214 , even though their typical short distance to their target cells has been estimated to cause insignificant conduction delay times 13 . Oligodendrocyte lineage cells can myelinate axons in an activity dependent manner and influence their conduction velocity properties 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the myelin remodeling observed on PV + axons after activity seems to mainly depend on changes in axon morphology rather than a released molecule. Indeed, axonal morphology predicts the myelin changes induced by activity (Stedehouder et al, ). This observation is in agreement with recent experiments showing that increasing the caliber of normally unmyelinated axons induces their myelination (Goebbels et al, ; Mayoral, Etxeberria, Shen, & Chan, ).…”
Section: Gaba In Neuron–oligodendroglia Communicationmentioning
confidence: 99%
“…While the implication of PV + interneuron activity on their own myelination has been confirmed (Stedehouder, Brizee, Shpak, & Kushner, 2018), the role of GABA receptors is uncertain. In a recent study, Stedehouder et al (2018) showed that the specific chemogenetic stimulation of PV + interneurons modifies the morphology and myelination of PV + axons without changing the total myelin content or the OL cell density. The activity of PV + interneurons seems therefore to specifically control the myelination of PV + axons.…”
Section: Gaba In Adaptive Myelinationmentioning
confidence: 99%
“…Since these early studies in the visual system, a wide range of animal models have been used to investigate the responsiveness of myelination to either environmental input or neuronal activity. These diverse approaches include stimulating or blocking activity in myelinating co‐cultures (Demerens et al, ; Lundgaard et al, ; Stevens, Porta, Haak, Gallo, & Fields, ; Wake, Lee, & Fields, ), social isolation or environmental deprivation (Hughes, Orthmann‐Murphy, Langseth, & Bergles, ; Liu et al, ; Makinodan, Rosen, Ito, & Corfas, ; Narducci et al, ), motor training (McKenzie et al, ; Sampaio‐Baptista et al, ), optogenetic, electrophysiological, or chemogenetic stimulation of neurons in the mouse brain (Gibson et al, ; Li, Brus‐Ramer, Martin, & McDonald, ; Mitew et al, ; Stedehouder, Brizee, Shpak, & Kushner, ) or genetic modulation of neuronal firing and vesicular release in the zebrafish (Hines, Ravanelli, Schwindt, Scott, & Appel, ; Koudelka et al, ; Mensch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether signaling from active axons to the mature myelin also results in active modification of the myelin sheath remains unclear. BDNF, brain-derived neurotropic factor; OPC, oligodendrocyte progenitor cell Makinodan, Rosen, Ito, & Corfas, 2012;Narducci et al, 2018), motor training (McKenzie et al, 2014Sampaio-Baptista et al, 2013), optogenetic, electrophysiological, or chemogenetic stimulation of neurons in the mouse brain (Gibson et al, 2014;Li, Brus-Ramer, Martin, & McDonald, 2010;Mitew et al, 2018;Stedehouder, Brizee, Shpak, & Kushner, 2018) or genetic modulation of neuronal firing and vesicular release in the zebrafish (Hines, Ravanelli, Schwindt, Scott, & Appel, 2015;Koudelka et al, 2016;Mensch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%